Review of Literature for Dissertation: Why and How? (Advancements in Homeopathic Research, 2023)
Literature review adds legitimacy to the study which  is primarily scrutinized to spot gaps of knowledge in  that area of specialization. Review of Literature is  also required to deciding the topic and strengthens the  rationale of undertaking a particular research project.  This article tries to throw light on a few common  difficulties faced by the researchers particularly PG  students while writing dissertations and remedial  measures that can be taken into account to achieve  this objective.
Keywords: Literature review; research project; specialization